2006
DOI: 10.1188/06.onf.105-112
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Context of Mammography Screening Use

Abstract: Theoretically based cultural beliefs are important to consider for behavioral interventions to increase mammography screening in African American and Caucasian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
57
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 30 publications
5
57
3
1
Order By: Relevance
“…Similar to our study, Russell and colleagues (65) determined that perceived benefits was not influential on routine mammography screening and that only low barriers increased mammography rates. In another study, there was no correlation between perceived benefits and mammography behavior, while a low barrier was reported to be effective in mammography (62).…”
Section: Discussionsupporting
confidence: 75%
“…Similar to our study, Russell and colleagues (65) determined that perceived benefits was not influential on routine mammography screening and that only low barriers increased mammography rates. In another study, there was no correlation between perceived benefits and mammography behavior, while a low barrier was reported to be effective in mammography (62).…”
Section: Discussionsupporting
confidence: 75%
“…The same study determined a negative, weak, and insignificant (r = -0.29) relation between the perceived sensitivity and having mammography (39). However, there are also studies asserting that there is no significant relation between the perceived sensitivity and having mammography (14,40). The fact that the sensitivity perception was high in the present study might have been caused by the women considering themselves at risk simply due to being women.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, we determined that illiterate single women without health insurance who did not have a history of mammography had a higher barrier perception. In their 5-year study, Russell et al (40) examined the effect of health beliefs on the frequency of having mammography, finding that participation in screenings was associated with the participants' educational level. In a study performed with Chinese-American women aged 40-85 years, Yu and Wu stated that access to medical services, perceived barrier, and information search behavior were all effective for promoting the use of mammography services (45).…”
Section: Discussionmentioning
confidence: 99%
“…While those who perceived themselves "not at all likely" to develop CKD may have been less likely to adhere to prescribed therapies due to a lack of perceived need, persons who perceived themselves as "very likely" to develop CKD may have had fatalistic attitudes about the benefit of adherence on adverse outcomes. Studies in other areas have demonstrated fatalistic attitudes regarding the inevitability of disease may contribute to poor adherence rates [31][32][33][34] and that persons who perceive their ability to control their health are better able to adhere to medical regimens for chronic illnesses. [35][36][37] Greater perceptions of risk might also be associated with other attitudes we did not measure (e.g.…”
Section: Discussionmentioning
confidence: 99%